A PONTUAÇÃO COMOMOVIMENTOS DO SUJEITO NA ESCRITA: PONTOS DE REFLEXÃO - Dallarosa, Andréia Rodrigues Zoelner (2013)
In this study I understand the language as an element constructed from the interaction, which is effective as a subjectin a linguistic-discursive movement, and the acquisition of writing asa process that occurs through out thelifeof the subject, given the graphical societywe live in.Although the teachingof the mother language-includingthe punctuation-is present throughout theschool lifeof the subject, and beyond, ison the Classes of Portuguese Language that has fallen all the responsibility on teaching issues involving, among other aspects,reading and writing texts. The punctuation, constituent elementof writing productions,is generally associated with speechand reading,even by under graduates in Letters, future teachers. These students come to University after,at least,eleven years ofbasic schooling, it is assumed, then, that have prior knowledge about the punctuation, which derive,a certain extent, the uses to which it does.However, through out the course, with the expansion of literacy, how to punctuate may change, so I try to analyzethe punctuationas a constituent elementof the construction of meaning in texts students a Letras teaching qualification, which occur by signs which I under standas markers elements syntactic, semantic, prosodicand discursive.Writing presupposes an Other, which one we wish create, and the punctuation is a mechanism that organizesandrelates this writing.From theseideas, we began theres earch project that led to this dissertation, whose questionis: during the production processof a text, as the punctuationis perceived and performed by students from the course of Letters and that Other interference involvedin this use,contributing to the constructionof themeaning of the text?Whereasthe writing process andtext producedfostera reflection onwhat is said, I recognize that the language intheirwritingachievementsurpassesthe functions assignedby the grammarrules,especially as it presentsasan element insocial relations, because it actson thesubject,meaning him. This study was basedonBernardes(2002, 2005), CláudiaLemos(1989,1995, 1998, 1999, 2001, 2002),proposesthatthe theoretical basis ofinteractionismadopted in this study; DahletVéronique(2002, 2007),Bernardes(2002, 2005), LawrenceChacon(1997, 2003), authorswho studythe punctuation andCarloGinzburg(1989) conceived theresearch methodused,calledevidential paradigm.The textsselected foranalysiswere produced bystudents from theLetras teaching qualification, during the firstgraduation year, time that the students begin tomake contactwithmoredirectedconceptions of languagedifferentfrom that foundin the manualsofgrammar. Wereselected to formthecorpusof this researchthirty-fivewritten textsproducedby threeacademics, analyzedunder themethodological approachofevidentiary paradigm. Regardingpunctuation, I understand that they do not representpausesin speech orreadingin the writing,butrelateto the rhythmof the writingitself, an organizer to the rhythmof writing(Meschonnic, 2006). Thepunctuationcollaborateto build the elaborationsyntactic, semantic, prosodicanddiscursive inthe text.Thesesigns constituteitself as asubjectivetraitthat emergesat the time of production, functioning asa mark, a signatureof the author. Key-words:Writing;Interactionism; Punctuation; Subject.